การจัดเส้นทางการขนส่งต่อเนื่องหลายรูปแบบและควบรวมสินค้า - ธนัท รุ่งวาณิชสุขานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research presents a study on Multimodal and Consolidation Routing Problem. The research aim to apply the knowledge from Operation Research (OR) to develop a mathematical model that can handle this problem. The Multimodal Network in this research refers to the transportation network of Truck and Air Transportation. The complexity of the problem is the different between the characteristics of Truck and Air Transportation. Truck transportation is Flexible Time Service on the other hand Air transportation is Scheduled Time Service so the research has to formulate model that can synchronize the time schedule of this two modes together in an efficient way. To develop the mathematical model in this research, the researcher applies the concept of Shortest Path Problem with Time Window and Multi-Commodity Flow Problem together, as the result this research present the mathematical model in two forms that are Node-Arc Based Formulation and Path Based Formulation and also apply the Column Generation procedure to solve the Path Based Formulation. The result shows that the developed model can handle the Multimodal and Consolidation Routing Problem in an efficient manner.